(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, eMeO MSf Hf HGbQ Hf YHO GdQMje, J (B1202(3g`s ((3ESeGYjd Hf MSf Ydj GdfLa CHGOjs)
(3ChdgG (B:s
(3ef GdCbSGe GdCQHYI GdJj Hfj YdjgG GdcJGH aj GdYbhO, LeY YbO, hgh dZI VO GdMd(B...s
(3BNQgG (B:s
(3CeG GdKGfj agh hGVM GdaSGO hcja cGf aMed GdYHGQI Ydi Pdc eecf hEf cGf HYjOG Hd QHeG fhbT ajeG SeYJg ef hLhg GdETcGd(B... (3Je GdeLdO GdKGdK ef GdYbhO(B... (3hjJdhg GdQHGY aj GdVeGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B214s
(3EjVGM Gdecfhf(B: (3L(B1(3, U(B378s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis